Stable Packaging of Phage PRD1 DNA Requires Adsorption Protein P2, Which Binds to the IncP Plasmid-Encoded Conjugative Transfer Complex - Grahn, A. Marika (American Society for Microbiology, 1999)
The double-stranded DNA bacteriophage PRD1 uses an IncP plasmid-encoded conjugal transfer complex as a receptor. Plasmid functions in the PRD1 life cycle are restricted to phage adsorption and DNA entry. A single phage structural protein, P2, located at the fivefold capsid vertices, is responsible for PRD1 attachment to its host. The purified recombinant adsorption protein was judged to be monomeric by gel filtration, rate zonal centrifugation, analytical ultracentrifugation, and chemical cross-linking. It binds to its receptor with an apparent K(d) of 0.20 nM, and this binding prevents phage adsorption. P2-deficient particles are unstable and spontaneously release the DNA with concomitant formation of the tail-like structure originating from the phage membrane. We envisage the DNA to be packaged through one vertex, but the presence of P2 on the other vertices suggests a mechanism whereby the injection vertex is determined by P2 binding to the receptor.